2020
DOI: 10.1021/acscatal.0c01559
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dual-Catalysis: A Sequential Michael Addition/Asymmetric Transfer Hydrogenation of α-Nitrosulfone and Enones

Abstract: Development of an efficient cocatalyst system to eliminate the intrinsic conflict of the cross-interactions in a pair of cocatalysts and to overcome the extrinsic conflict of the reaction conditions in an unmatched reaction environment has great significance in asymmetric dual catalysis. Herein, a compartmentalization method involving the integration of a cocatalyst system has been developed, which enables an efficient Michael addition/reduction enantioselective dual-catalysis process to be accomplished from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In particular, the TEM image with a chemical mapping demonstrated that the rhodium centers in 5 were uniformly distributed (Figure 2c). Furthermore, the nitrogen adsorption‐desorption isotherms of 5 also confirmed its mesoporous structure, since a typical IV character with an H 1 hysteresis loop was observed that was the same as those reported for hollow‐shell‐structured mesoporous silica (see Figure S7 of ESI) [10c] …”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…In particular, the TEM image with a chemical mapping demonstrated that the rhodium centers in 5 were uniformly distributed (Figure 2c). Furthermore, the nitrogen adsorption‐desorption isotherms of 5 also confirmed its mesoporous structure, since a typical IV character with an H 1 hysteresis loop was observed that was the same as those reported for hollow‐shell‐structured mesoporous silica (see Figure S7 of ESI) [10c] …”
Section: Resultssupporting
confidence: 77%
“…It was found that the thermoresponsive polymer‐coating layer in 5 was necessary because the cascade reaction either at 20 °C or 40 °C gave the final ( S )‐ 6 a with the obviously decreased yields and ee values. This was attributed to the swelling conformational state of the thermoresponsive polymer‐coating layer in 5 at >10 °C proven by a turbidity investigation of 5 (see Figure S8 of ESI) [10c,13a] . During this process, the first‐step oxidation and the second‐step reduction simultaneously proceeded.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…This superiority offers a practical opportunity for the one-pot hydration/reduction of alkynes to overcome the limitations of environmental issues, high cost, and/or the harsh conditions originating from noble metal/ligand catalysts. Due to the benefits of the compatibility of the mild catalysis condition of cobaloximes with the Rh/diamine catalyst, and taking into account our recent progress in silica-based chiral recyclable heterogeneous catalyst through a covalent-bonding method (Chang et al, 2020;Li et al, 2021;Zhao et al, 2021), we envision that via a one-pot hydration/ATH catalyzed with a combination of inexpensive cobaloximes (Schrauzer, and Windgassen, 1967;Bakac et al, 1986;Geno, and Halpern, 1987;Hou et al, 2017) and DMONs-based Rh/ diamine as co-catalysts (Hashiguchi et al, 1995;Hannedouche et al, 2004;Matharu et al, 2005;Hayes et al, 2005;Ohkuma et al, 2006;Cheung et al, 2007;Touge et al, 2011;Touge et al, 2016), the alkynes could be converted into chiral alcohols. As presented in this study, this sequential enantioselective organic transformation, an initial homogeneous cobaloxime-catalyzed hydration of alkynes followed by a subsequent heterogeneous Ru/diamine-catalyzed ATH transformation of in-situ generated ketones, provided various chiral alcohols in good yields and up to 99% ee.…”
Section: Introductionmentioning
confidence: 99%